Digitalisation of Public Administration Services as Part of Digital Economy Development in Post-war Ukraine - Mariia Rysin; Oleksandr Babych (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: This paper explores the pivotal role of the digitalisation of public administration services as part of the development of the digital economy in post-war Ukraine. It aims to analyse how this factor contributes to rebuilding and modernising the nation’s economic and administrative frameworks in the aftermath of conflict.